Involvement of ribosomal protein L7/L12 in control of translational accuracy. - Kirsebom, L A (1985)
The effects of two mutations, which map at the rplL locus and both give a changed 50S ribosomal protein L7/L12, were studied. Both mutations are associated with an increased misreading of all three nonsense codons in vivo and ribosomes from the mutants give an increased misreading of the phenylalanine codon UUU by tRNALeu in vitro. The rplL-associated misreading in vitro is not limited to a particular type of mRNA or tRNA. Results from a translational proofreading assay, using mutant ribosomes, suggest that protein L7/L12 is involved in the control of translational accuracy by contributing to the efficiency of a translational proofreading step(s).